PENGUKURAN KINERJA DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD PADA UNIT PENGELOLA KEGIATAN (UPK) SYARIAH MANDIRI KECAMATAN SELAKAU - Aurellia, Elita; Nashirun (Sebi : Studi Ekonomi dan Bisnis Islam, 2024)
The Syariah Mandiri Activity Management Unit (UPK) Selakau District conducts performance measurements at the Syariah Mandiri Activity Management Unit (UPK) Selakau District using only a financial perspective. The Syariah Mandiri Activity Management Unit (UPK) Selakau Sub-District has not conducted performance appraisals in the perspective of customers or members' views, performance measurements in the perspective of internal processes, and performance appraisals in the perspective of learning and growth. Therefore, researchers are interested in measuring the performance of the Syariah Mandiri Activity Management Unit (UPK) Selakau District, using the Balanced Scorecard method because it is a very appropriate method used to assess performance in the Syariah Mandiri Activity Management Unit (UPK) Selakau District, because the Balanced Scorecard method not only assesses in financial terms but also assesses in non-financial terms. The focus of the problem in this study is: How is the performance of the Independent Sharia Activity Management Unit (UPK) Selakau District seen from the use of the Balanced Scorecard approach?. This research method uses a qualitative approach. Then in this study using a type of descriptive qualitative research. Data collection techniques used based on primary data are observation, interviews and documentation. Then the secondary data are profile data of the Activity Management Unit (UPK) Selakau District, archives, books, journals, income statements and balance sheets. Based on the results of field research, it can be concluded that performance from a financial perspective has decreased profit and loss as seen from the income statement data of the Sharia Mandiri Activity Management Unit (UPK), Selakau District. Therefore, financial performance is measured to be not good overall due to a decrease in profits from 2020-2022. Performance from the customer's perspective on the number of customers always increases. This can be measured as a whole, the increase occurred from 2020-2022, showing a good performance from the perspective of good customers from the Syariah Mandiri Activity Management Unit (UPK), Selakau District, in obtaining customers. Performance from the perspective of internal business processes has increased as seen from transaction value data and the growth rate of the Syariah Mandiri Activity Management Unit (UPK), Selakau District. It can be measured that the perspective of internal business processes is good enough. Performance in the perspective of growth and learning decreased as seen from the productivity data of employees of the Syariah Mandiri Activity Management Unit (UPK), Selakau District. This suggests that the performance of growth and learning perspectives can be measured not well.